Acoustic power transfer for biomedical implants using piezoelectric receivers: effects of misalignment and misorientation. (13th June 2019) - Basaeri, Hamid; Yu, Yuechuan; Young, Darrin; Roundy, Shad
Abstract: Implantable medical devices (IMDs) can be powered wirelessly using acoustics with no need for a battery. In an acoustic power transfer system, which consists of a transmitter, medium, and a receiver, the power that the receiver generates is a function of its position (depth, orientation, and alignment relative to the transmitter). The power delivered to the implant should remain stable and reliable even with possible uncertainties in the location of the implant. In this paper, we compare two common designs for piezoelectric ultrasonic transducers that can be used for acoustically powering IMDs, and study their generated power sensitivity to any change in their location. Although commercial off-the-shelf (COTS) transducers are widely being used in the literature, they may not be the best candidate for powering small implants since they may not be able to provide sufficient power in the presence of location uncertainties. Piezoelectric micromachined ultrasonic transducers (pMUTs) are diaphragm structures and are also suitable for wirelessly powering implants. We present a pMUT receiver and study the sensitivity of the generated power of the pMUT to changes in its position. We then perform a comparative study between power generation capability of our pMUT and a COTS transducer with the same lateral dimensions as the pMUT. We observed that the generated power from a pMUT structure is less sensitive to misorientation and misalignment of the device. The average percentage improvement in the generated power from pMUT compared to COTS are 86%, 917%, and 111% for depth, alignment, and orientation, respectively.